A eficácia da fibrina rica em plaquetas em exodontias de terceiros molares inferiores: uma revisão de literatura - Matos, Gabriel Carvalho (2021)
The removal of mandibular third molars is one of the most commonly performed surgical procedures in dentistry, however, it is often accompanied by associated inflammatory events, with pain, trismus and edema being the most commonly reported. In this context, Fibrin Rich in Platelets (FRP), has been used in several surgical procedures due to its benefits in reducing postoperative morbidity. It presents itself as one of the most promising alternatives for an autologous source of cytokines and growth factors capable of favoring tissue repair. The aim of the study was to review and discuss the literature on the use and effectiveness of FRP in extractions of lower third molars. A bibliographic survey was carried out by consulting the PubMed, Web of Science, Scopus and Lilacs databases. The following descriptors were used together: “platelet-rich fibrin”, “third molar” and “surgery”. The selection of articles was based on the year of publication, being restricted to the last ten years (2010 to 2020), the English language, and those in which the full text was available. Articles involving randomized clinical case studies and systematic reviews with and without meta-analysis about the use of FRP after extraction of lower third molars were selected. Articles that were not related to the proposed theme were excluded, in addition to literature reviews, opinion articles and case reports. 24 articles were selected to carry out this literature review. Regarding the pain variable, 11 (45.8%) articles showed significantly statistical differences in their studies, 4 (16.6%) articles showed no differences and 9 (37.5%) articles did not report. In the edema variable, 10 (41.6%) articles showed significantly statistical differences; 3 (12.5%) articles did not present differences and 11 (45.8%) articles did not report. In the variable trismus, 1 (4.1%) article showed a statistically significant difference, 5 (20.8%) articles did not present differences and 18 (75%) articles did not report. In the variable soft tissue repair, 7 (29.1%) articles showed significantly statistical differences, 5 (20.8%) articles did not present differences and 12 (50%) did not report. Finally, in the bone repair variable, 5 (20.8%) articles showed significantly statistical differences, 7 (29.1%) did not show differences and 12 (50%) did not report. Thus, we can see that there is a need for further studies in order to obtain conclusive results on the real effectiveness of FRP in extractions of lower third molars.